Bridging Leader’s Personality with Leadership Style - Liu, Yao; Yan, Shao Qin; Sui, Hai Juan; Freida, Ayodele Ozavize; Feng, Li (Medwell Journals, 2017)
Purpose effective leaders have been increasingly regarded conclusive in achieving business success under today’s globalization. The study explores from the perspectives of leader’s personality and leadership style. The 16 personality global factors are adopted to identify the five personality traits including extraversion, anxiety, tough-mindedness, independence and self-control. Leadership styles are targeted at the task-oriented, the relations-oriented and the change-oriented. The 31 pairs of managers and their subordinates from telecommunication industries in Malaysia are invited for respective participation. The results show that) the dominant personality of leaders is extraversion followed by self-control; the most popular leadership style is task-oriented and the task-oriented leadership is line within dependence and self-control for change-oriented leaders they are extravert but less tough-mindedness and for relations-oriented leaders they are extravert and also independent. Future, researches are recommended to broaden the research scope from personality, leadership style to include leadership effectiveness which might be more beneficial for industries to build up their competitiveness. The study established the matrix demonstrating the relationships between each personality and leadership style which can be applied as guidance in industries for recruiting, selecting and promoting suitable person for proper managerial position.